2011
DOI: 10.4102/ajlm.v1i1.4
|View full text |Cite
|
Sign up to set email alerts
|

Identifying HIV infection in South African women: How does a fourth generation HIV rapid test perform?

Abstract: BackgroundHIV rapid tests (RT) play an important role in tackling the HIV pandemic in South Africa. Third generation RT that detect HIV antibodies are currently used to diagnose HIV infection at the point of care. Determine Combo (DC) is the first fourth generation RT that detects both p24 antigen (p24Ag) and HIV antibodies (Ab), theoretically reducing the window period and increasing detection rates. Early detection of maternal HIV infection is important to mitigate the high risk of vertical transmission asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 6 publications
0
12
0
Order By: Relevance
“…Multiple studies concluded that the performance of the Determine test was poor for detecting acute HIV, [ 31 , 36 39 , 44 , 46 ] and this meta-analysis provides evidence that the Determine Combo test, in its present form, is more suitable for use in testing/screening those populations which have already seroconverted. It should be noted that the accuracy of this test independent of the antibody component is only relevant for the period preceding seroconversion (the acute phase), when an antibody test would be negative.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Multiple studies concluded that the performance of the Determine test was poor for detecting acute HIV, [ 31 , 36 39 , 44 , 46 ] and this meta-analysis provides evidence that the Determine Combo test, in its present form, is more suitable for use in testing/screening those populations which have already seroconverted. It should be noted that the accuracy of this test independent of the antibody component is only relevant for the period preceding seroconversion (the acute phase), when an antibody test would be negative.…”
Section: Discussionmentioning
confidence: 73%
“…Three studies (Patel et al, Laperche et al, and Bhowan et al) each contained more than one separate, unique evaluation of the Determine Combo test, and in these cases each evaluation was treated independently. [ 31 , 39 , 41 ] Individual study estimates with their confidence intervals are represented through forest plots as seen in Fig 2 . Raw data extracted from each individual study can be seen in S2 Table .…”
Section: Resultsmentioning
confidence: 99%
“…Other studies concur that the Combo RT offers no advantage over 3rd generation rapid tests in its lack of ability to detect acute HIV infections. 16 Perhaps the p24 antigen levels were lower at the baseline visit and the sensitivity of the antigen detection component of Combo RT is influenced by the timing of testing. One of the many challenges of detecting acute HIV infections is the very short "window period" and a mere assumption of the midpoint of seroconversion.…”
Section: Discussionmentioning
confidence: 98%
“…The Determine HIV-1/2 Ag/Ab combo rapid test is the first such test that detects both Ag and Ab in two separate indicator lines. Early data on the performance of the Determine combo test to detect acute HIV infections in seroconversion panels suggested that it had a good performance in detecting early infections (19,20 (21)(22)(23)(24)(25)(26)(27)(28). Several of the studies were limited by small sample size and failure to follow up potential acute infections for seroconversion.…”
mentioning
confidence: 99%